Assessment of the engineering properties and economic advantage of recycled aggregate concrete developed from waste clay bricks and coconut shells. (1st June 2023) - Liu, Haibao; Li, Qiuyi; Wang, Peihan
Abstract: Using recycled aggregates to replace natural aggregates in concrete helps preserve nonrenewable resources, promotes recycling, and affords reductions in cost. To this end, experiments were performed to clarify the effects of coarse aggregate systems developed using crushed coconut shell aggregate (CCSA) and recycled brick aggregate (RBA) on the mechanical properties, thermal conductivity, ultrasonic pulse velocity and high temperature resistance of concrete. The results showed that the incorporation of CCSA improved the thermal conductivity, flexural strength and cost ratio of concrete. The mechanical properties of the recycled aggregate concrete also satisfied the requirements of structural lightweight aggregate concrete. In addition, low-rigidity concrete developed using RBA and CCSA imparted the building with a higher strain capacity, suitable for applications in seismic regions. However, under high-temperature environments, the properties of the concrete deteriorated significantly with the incorporation of CCSA; the compressive strength and other properties were also reduced considerably. Highlights: Using agricultural by-products and construction waste to produce recycled coarse aggregates. The workability, mechanical properties, thermal conductivity, high temperature resistance and economic of recycled aggregate concretes were studied. The low-rigidity structural concrete prepared with crushed coconut shell aggregate and recycled brick aggregate endows the building with higher strain capacity.